Igneous Rock Associations 18. Transition Metals in Oceanic Island Basalt: Relationships with the Mantle Components - Greenough, John; MacKenzie, Kevin (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2015)
Incompatible elements and isotopic ratios identify three endmember mantle components in oceanic island basalt (OIB); EM1, EM2, and HIMU. We estimate compatible to mildly incompatible transition metal abundance trends (Ni, Co, Fe, Cu, Cr, V, Mn, Sc, and Zn) in ‘primitive’ basalt suites (Mg# = Mg/(Mg + 0.9*Fe) atomic = 0.72) from 12 end-member oceanic islands by regressing metals against Fe/Mg ratios in sample suites, and solving for concentrations at Mg/Fe = 1 (Mg# = 0.72). Using the transition metal estimates, exploratory statistics reveal that islands ‘group’ based on mantle component type even when La/Yb ratios are used to compensate metal concentrations for percentage melting. Higher chalcophile Zn (and Pb, earlier work) in EM1 and EM2 compared to HIMU, and higher Cr (3+) and Sc in HIMU relative to EM1, support views that HIMU represents subductionprocessed ocean floor basalt. Incompatible elements, ratios and isotopes indicate that EM1 is Archean, EM2 is Proterozoic or younger, and both are related to sediment subduction. As found with incompatible elements, EM1 and EM2 show similar ‘compatible’ element concentrations, but lower (multivalence) Cr, Fe and Mn in EM1 could indirectly reflect increasing oxidation of subducted sediment between the Archean and Proterozoic. Alternatively, changes in subduction processes that yielded peak continental formation in the Neoarchean, and craton-suturing in the Paleoproterozoic may account for EM1–EM2 differences. EM1 shows similar or lower Cr, Ni and Co compared to HIMU and EM2 suggesting that economic viability of layered intrusions, which have extreme EM1-like signatures, is unrelated to high metals in EM1 mantle sources, but that high % melting appears important. Because core-concentrated transition metals correlate with mantle component type, lithospheric recycling apparently controls their concentrations in OIB and core-mantle interaction may be unimportant.